2023
DOI: 10.1021/acsami.3c04531
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role Played by Interface Engineering in Weakening Thickness Dependence of Superconducting and Structural Properties of FeSe0.5Te0.5-Coated Conductors

Abstract: Increasing the thickness of a superconducting layer and simultaneously reducing the thickness effect in iron-based superconducting coated conductors are particularly essential for improving the critical current I c . Here, for the first time, we have deposited high-performance FeSe 0.5 Te 0.5 (FST) superconducting films up to 2 μm on LaMnO 3 -buffered metal tapes by pulsed laser deposition. An interface engineering strategy, alternating growth of a 10 nm-thick nonsuperconducting FST seed layer and a 400 nmthic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Notably, the J c value reaches a remarkable value of 8.2 × 10 5 A/cm 2 at 2 K, which is four times larger than that observed in pure NbSe 2 . The J c value of the (InSe 2 ) 0.12 NbSe 2 sample is larger than those of other TMD superconductors, such as NbS 2 , Cu x TiSe 2 , and Fe x NbSe 2 , and is comparable to other unconventional superconductors such as cuprate and iron-based superconductors. …”
mentioning
confidence: 84%
“…Notably, the J c value reaches a remarkable value of 8.2 × 10 5 A/cm 2 at 2 K, which is four times larger than that observed in pure NbSe 2 . The J c value of the (InSe 2 ) 0.12 NbSe 2 sample is larger than those of other TMD superconductors, such as NbS 2 , Cu x TiSe 2 , and Fe x NbSe 2 , and is comparable to other unconventional superconductors such as cuprate and iron-based superconductors. …”
mentioning
confidence: 84%
“…The FeSe0.5Te0.5 on a rolling-assisted biaxially textured substrate (RABiTS) exhibited Tc > 20 K. The self-field Jc reached 1 MA/cm 2 at 4.2 K, and Jc remained around 1 × 10 5 A/cm 2 under a high magnetic field of 30 T. Sylva et al found that the CeO2 layer plays an important role in preventing the element diffusion from the Ni-W substrate and inducing in-plane texture [81,82]. Song et al adopted an interface engineering strategy to mitigate the thickness effect, successfully fabricating micron-thick FeSe0.5Te0.5 superconducting films on IBAD-LaMnO3-buffered metal tapes [65]. Unlike the continuous growth mode, the alternating growth of a 10 nm thick seed layer and a 400 nm thick FST superconducting layer ensures the crystalline quality of FeSe0.5Te0.5 films (see Figure 17a-c).…”
Section: Fabrications Of Meters-long Fete1−xsex-coated Conductors And...mentioning
confidence: 99%